Effect of “Tell Show Do” Method on Dental Anxiety in Pediatrics Dentistry: A Meta Analysis - Cahyani, Mey Ditaputri; Widyaningsih, Vitri; Prasetya, Hanung; Simatupang, Nanda Agustian (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Anxiety in children will make it difficult for dentists to perform dental treatment. In dentistry, especially pediatric dentistry, children who are very anxious will avoid examinations and refuse dental treatment. This study aims to analyze the influence of the